1992
DOI: 10.1037/h0079371
|View full text |Cite
|
Sign up to set email alerts
|

Parental death in childhood: Perceived vulnerability, and adult depression and anxiety.

Abstract: College students who had experienced the death of a parent during their childhoods perceived themselves as more vulnerable to future losses than did a nonbereaved control group. Perceived vulnerability to loss was identified as a better predictor of adult anxiety and depression than was the early loss itself. Perceived vulnerability to loss is thus implicated in the development of adult psychopathology associated with early loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 29 publications
0
35
0
3
Order By: Relevance
“…By so doing, he allowed a greater artistic expression of grief while at the same time reinforcing that Twick had been a family member. Resolution of childhood grief is critical, for unresolved childhood grief and perception of vulnerability to loss result in impaired adult relationships and increased adult psychopathology (Agid et al, 1999;Edmans & Marcellino-Boisvert, 2002;Mireault & Bond, 1992). Nonetheless, recent research suggests that emotional disclosure does not facilitate adjustment to loss in normal bereavement (Stroebe, Schut, & Stroebe, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…By so doing, he allowed a greater artistic expression of grief while at the same time reinforcing that Twick had been a family member. Resolution of childhood grief is critical, for unresolved childhood grief and perception of vulnerability to loss result in impaired adult relationships and increased adult psychopathology (Agid et al, 1999;Edmans & Marcellino-Boisvert, 2002;Mireault & Bond, 1992). Nonetheless, recent research suggests that emotional disclosure does not facilitate adjustment to loss in normal bereavement (Stroebe, Schut, & Stroebe, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Suicide (Crook & Raskin, 1975), alcoholism (Birtchnell, 1972), social introversion (Dietrich, 1984), and dependency (Birtchnell, 1975) have all been linked to childhood parental bereavement. Adults who experienced parental death during childhood have been found to predict a shorter life span for themselves (Denes-Raj & Ehrlichman, 1991), to worry more about their own death (Zall, 1994), and to perceive themselves as more vulnerable to future losses (Mireault & Bond, 1992) than individuals who are not parentally bereaved. Jacobson and Ryder (1969) found that adults who experienced early parental death had more difficulty sustaining intimacy and expressing anger than those who did not have a history of parental loss.…”
Section: Prior Researchmentioning
confidence: 98%
“…In children, early parental loss from death or separation engenders an increased risk for developing future psychiatric illnesses, such as major depression and anxiety (Mireault and Bond, 1992;Agid et al, 1999). For example, Romanian orphans who received little social support before age three and one-half displayed increased autistic-like behaviors (Rutter et al, 1999) and indiscriminate social behaviors (Chisholm, 1998;O'Connor and Rutter, 2000;Rutter and O'Connor, 2004).…”
Section: Introductionmentioning
confidence: 99%